Investigations on the mechanical and damping properties of styrene-butadiene rubber with graphene and carbon black - Sivakumar C.; Muralidharan V.; Ravikumar N.; Murali Manohar D. (FME Transactions, 2023)
An experimental and numerical study on the mechanical and damping properties of styrene-butadiene rubber (SBR) composites with graphene nanoparticles (GNP) and carbon black (CB) is presented in this paper. The composites were tested for mechanical properties such as hardness and tensile strength. It is observed that the composites with GNP & CB fillers have higher stiffness and percentage elongation for failure. A scale model of the chassis was subjected to forced vibration to find the damping properties of each of the prepared composites. The experimental results were used to create a numerical model in ANSYS software using Yeoh's hyper-elastic model to generate a hyper-elastic material to simulate the composite property and to perform harmonic response analysis in ANSYS. The results from experiments and theoretical findings exhibited good agreement.